Anticipatory stress, state policy contexts, and mental health during the COVID-19 pandemic - Mateo P. Farina; Zhe Zhang; Rachel Donnelly (Elsevier, 2023)
Substantial economic disruptions during the COVID-19 pandemic upended daily life and contributed to a widespread symptom of psychological distress during this period. Disruptions also led to more concerns about future stressful events related to financial hardship, or economic-related anticipatory stress, with the potential to undermine mental health. Although prior research provides ample evidence that state policies can impact mental and physical health, it has not considered how state policy contexts reduce adverse psychological outcomes stemming from economic-related anticipatory stress. The present study uses national survey data from the Census Bureau's Household Pulse Survey (April 2020-October 2020) to examine the extent to which state policy contexts moderate the association between economic-related anticipatory stress and depression/anxiety. We find that states with stronger social safety nets weakened the impact of anticipatory stress on depression/anxiety. This finding held for different types of anticipated economic hardships (i.e., reduced income, difficulty paying rent, difficulty affording food), as well as for policies that existed prior to COVID-19 and policies enacted in response to COVID-19. Findings provide strong evidence that state policies may buffer against poor mental outcomes for people who even anticipate facing economic uncertainty during the COVID-19 pandemic. We provide insight into how state policy contexts can shape individual experiences in ways that impact the mental health outcomes of the United States population.